Pengaruh Communication Marketing dan Brand Image pada Viral Marketing Terhadap Minat Beli Pelanggan Brand Erigo Store di Era New Normal - Muhammad Ainur Iqbal; Ety Dwi Susanti (Universitas Batanghari, 2022)
This study aims to determine the extent of the influence of Communication Marketing and Brand Image on Viral Marketing on Buying Interest of Erigo Store Brand Customers in the New Normal Era among Students in the City of Surabaya. In this study using quantitative methods with a descriptive approach. The data used in this study is the target population used in this study, namely active students of the Faculty of Social Sciences, veterans of UPN East Java, with a sample of 343 respondents. The tests used are validity and reliability tests to measure data quality, classical assumption test and path analysis. The results of this study can be seen that the results of the structure I: show that there is a positive influence by having a direct influence on the product of the erigo store. brand erigo has carried out its strategy optimally through good communication on social media and providing interesting content, and creating a good image of the brand and customer image so that the strategies and innovations provided provide curiosity for customers or followers on social media. In the results of structure II: the influence of marketing communication on asking to buy erigo products through viral marketing, where customers only admire the content provided by erigo where erigo is still improving its brand image so that it can go even wider to international, and also the lack of product innovation and the latest limited which can increase the customer's sense of belonging because the product is different from the others and results in customer satisfaction, especially among young people, including veterans of the Faculty of Social Sciences, UPN, East Java. The conclusion shows that the test results on the influence of marketing communications have an indirect effect on buying interest in erigo strore customers. From the results of the influence of brand image having a positive and significant influence on buying interest, these results show a good increase in the image of the Erigo store in the minds of customers, especially the students of FISIP UPN East Java, and indirectly lead to satisfaction with the ownership of an Erigo product that it offers. The better the brand image given to the Erigo brand customers, the more customer buying interest will increase. From the results of this viral marketing effect, it has a positive and significant influence on buying interest.